The Complete Rock Climber - Creasey, Malcolm [et.al] (London Hermes House, 2006)
"A comprehensive illustrated guide to every aspect of rock climbing, from basic indoor wall climbing techniques to the ultimate adventure of scaling sea cliffs and high mountain crags. For beginners, helpful advice is provided on essential clothing and equipment. Handholds and footholds are described and ropework skills for every eventuality are included. For those with more experience, information is provided on climbing in remote places and the special skills needed to do this safely and responsibly, including navigation, interpreting the weather and first aid" -- Publisher description.
Include Color Illustration and Index
Keywords: Rock climbing